PERBANDINGAN KEEFEKTIFAN MEDIA DIRE GAME (DIARRHEA PREVENTION GAME) DENGAN MEDIA POWERPOINT TERHADAP PENGETAHUAN DANSIKAP TENTANG PENCEGAHAN DIARE PADA SISWA SD NEGERI 006 LOA JANAN ILIR TAHUN 2024 - Ajeng Rahayu; Joko Sapto Pramono, Yona Palin T (Jurnal Kesehatan, 2025)
Introduction : During the growth and development period, elementary school age children often experience health problems such as diarrhea. Diarrhea can occur in all age groups, one of which is elementary school age children. The increase in diarrhea cases in the Harapan Baru area during the period 2021 to 2023. In 2021, there were 117 cases recorded and this increased to 152 cases in 2022, and reached the highest number in 2023, namely 223 cases. This research aims to analyze the comparison of the effectiveness of dire game media (diarrhea prevention game) with Powerpoint media on knowledge and attitudes about preventing diarrhea in students at SD Negeri 006 Loa Janan Ilir. Method : This type of research is pre-experimental using a two group pretest posttest design. The panel research sample consisted of 82 class V students. Data was collected through filling out a questionnaire. Data analysis used the Wilcoxon test and the Mann-Whitney test. Results : The results of the study showed that Dire Game Media was proven to be more effective than PowerPoint media in improving knowledge and attitudes, with P-values obtained from Dire Game media of 0.000 for knowledge and 0.000 for attitudes. In contrast, PowerPoint media showed a higher P-value, namely 0.140 for knowledge and 0.250 for attitudes. These findings indicate that Dire Game media has a more significant impact on diarrhea prevention efforts at SD Negeri 006 Loa Janan Ilir.Conclusion : The conclusion of this research is that Dire Game media is more effective for elementary school children compared to Powepoint media.